A survey of stream data mining - Ikonomovska, Elena; Loshkovska, Suzana; Gjorgjevikj, Dejan (My University, 2007)
At present a growing number of applications that generate massive streams of data need intelligent data processing and online analysis. Real-time surveillance systems, telecommunication systems, sensor networks and other dynamic environments are such examples. The imminent need for turning such data into useful information and knowledge augments the development of systems, algorithms and frameworks that address streaming challenges. The storage, querying and mining of such data sets are highly computationally challenging tasks. Mining data streams is concerned with extracting knowledge structures represented in models and patterns in non stopping streams of information. In this paper, we present the theoretical foundations of data stream analysis and identify potential directions of future research. Mining data stream techniques are being critically reviewed.
Keywords: data streams, data mining, review